FGL1 as a Novel Mediator and Biomarker of Malignant Progression in Clear Cell Renal Cell Carcinoma - Lv, Zheng; Cui, Bo; Huang, Xing; Feng, Hua-Yi; Wang, Tao; Wang, Han-Feng; Xuan, Yun-Dong; Li, Hong-Zhao; Ma, Xin; Huang, Yan; Zhang, Xu (Frontiers in Oncology, 2021)
Clear cell renal cell carcinoma (ccRCC), which is the most prevalent renal cell carcinoma subtype, has a poor prognosis. Emerging strategies for enhancing the immune response in ccRCC therapy are currently being investigated. Fibrinogen-like Protein 1(FGL1) is a novel mechanism that tumors may use to evade the immune system by binding LAG-3 and negatively regulating T cells. In this study, we aimed at investigating the underlying mechanism of FGL1 in ccRCC, and its expression and prognostic value. We found that FGL1 was upregulated in tumor tissues and plasma specimens of ccRCC patients. High FGL1 expression predicted a poor prognosis for ccRCC patients. We also discovered that overexpression of FGL1 enhances RCC cell migration, invasion, and metastasis by activating the epithelial-to-mesenchymal transition (EMT). Consistent with these results, we identified a significant positive correlation between expression of FGL1 and EMT-related genes through tissue microarray analysis. Gene-expression analysis revealed that FGL1-deficient ccRCC cell lines had altered transcriptional output in inflammatory response, cell-cell signaling, negative regulation of T cell activation, and intracellular signal transduction. Depletion of FGL1 significantly inhibited tumor growth and lung metastasis in orthotopic xenograft mouse model. Infiltration of myeloid-derived CD11b+ and Ly6G+ immune cells in tumor microenvironment (TME) was strikingly decreased when FGL1 expression reduced. Therefore, increased FGL1 expression in ccRCC is positively correlated with poor prognosis. Mechanistically, FGL1 facilitates the EMT process and modulates TME, which promotes ccRCC progression and metastasis. Consequently, targeting FGL1 can potentially improve clinical outcome of ccRCC patients.